Shear Behavior of Self Compacting Concrete - F. Atshan, Ali (Journal of Engineering and Sustainable Development, 2012)
Twelve self compacting concrete (SCC) beams were cast to investigate the shear behavior under two concentrated load. All beams have a constant longitudinal steel ratio of (0.02065) and constant gross section area of (17000)mm2. The tested beams were divided into two group with and without stirrups. The first group contained three beams without stirrup at different value of compressive strength ( ) with the same value of clear span to the effective depth ratio (ln/d), while the second group contained nine beams with stirrups. This group was divided into three series according to the compressive strength ( ) each series contained three beams at different value of clear span to effective depth ratio(ln/d).It was found that the ultimate shear strength predicated from ACI 318-08 is lesser than the experimental values. The ultimate shear strength for SCC beams with stirrups increase about 15.73%.30.69 %and 25.633 % when the compressive strength increased from (29.36 to 49.2 MPa) at clear span to effective ratio (ln/d) 6.164, 5.479 and 5.0 respectively. The ultimate shear strength for SCC beams without stirrups increased about 31.25% when the compressive strength increased from (29.36 to 49.2 MPa),.....